2010
DOI: 10.1002/eji.200940232
|View full text |Cite
|
Sign up to set email alerts
|

Does TLR2 regulate intestinal inflammation?

Abstract: There is almost no aspect of the immune response that is not regulated by TLR. Initially described as drivers of the innate immune response to pathogens, it is now clear that the TLR family can also influence most aspects of adaptive immunity, as well as determine how tissue cells interact with microbes in their environment. In particular, the intestine and its immune system must co-exist with an enormous community of commensal bacteria and are also on constant alert against invading pathogens. Unsurprisingly,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 21 publications
(31 reference statements)
0
9
0
Order By: Relevance
“…In contrast to the above findings, which have alluded to the important role of TLR signaling in T effector and regulatory functions, some reports indicate that TLR-costimulation in T cells leads to enhanced autoreactivity in certain conditions, such as autoimmune arthritis, systemic lupus erythematosus (SLE) and multiple sclerosis (Himmel et al 2008;Marta 2009;Mowat 2010). For example, a microbial lipoprotein, Lip-Osp A from Borrelia burgdorferi (the causative agent of Lyme disease), was shown to induce a TLR2-dependent autoimmune arthritis in C57BL/6 mice (Sobek et al 2004).…”
Section: Tlr-costimulation In T Cells and Autoimmunitymentioning
confidence: 87%
“…In contrast to the above findings, which have alluded to the important role of TLR signaling in T effector and regulatory functions, some reports indicate that TLR-costimulation in T cells leads to enhanced autoreactivity in certain conditions, such as autoimmune arthritis, systemic lupus erythematosus (SLE) and multiple sclerosis (Himmel et al 2008;Marta 2009;Mowat 2010). For example, a microbial lipoprotein, Lip-Osp A from Borrelia burgdorferi (the causative agent of Lyme disease), was shown to induce a TLR2-dependent autoimmune arthritis in C57BL/6 mice (Sobek et al 2004).…”
Section: Tlr-costimulation In T Cells and Autoimmunitymentioning
confidence: 87%
“…Namely, whole TABLE 3. Bacterial species with significant difference in abundance between Tlr2 Ϫ/Ϫ (TLR- [1][2][3][4][5] and WT (11)(12)(13)(14)(15)(16)(17)(18)(19)(20) genomic interrogation of DNA methylation changes showed that ϳ1.4% of the colonocyte genome is modified epigenetically in Tlr2 Ϫ/Ϫ mice. These changes were associated more with CpG islands, gene promoters, DNase I hypersensitive regions, and CTCF-binding sites than control regions.…”
Section: Discussionmentioning
confidence: 98%
“…However, in chronic intestinal inflammation, such as that induced by adoptive transfer of naïve CD4 + T cells into mice lacking adaptive immunity (RAG1-deficient mice), TLR2 signaling does not affect gut pathology 26 . Therefore, TLR2 signaling may confer protection against acute mechanical injury through maintenance of tight junction integrity while having minimal effects on regulation of sustained inflammatory processes.…”
Section: Tlr2 and Its Co-receptors Tlr1 And Tlr6mentioning
confidence: 99%